2018
DOI: 10.1111/geb.12702
|View full text |Cite
|
Sign up to set email alerts
|

A new macroecological pattern: The latitudinal gradient in species range shape

Abstract: Aim We analyse the latitudinal variation of range shape, testing whether ranges at higher latitudes or of larger size tend to be elongated in an east–west direction, as expected from climatic niche constraints. Additionally, we assess whether poleward range limits are less stochastic than equatorward limits. Location Global; all terrestrial areas except Antarctica. Time period Contemporaneous. Major taxa studied Birds and mammals. Methods We quantified the shape of the distribution ranges of 10,057 species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…relative longitudinal and latitudinal extent) can help disentangle the importance of barriers compared to environmental gradients (Brown & Maurer, ). For instance, a study of gradients in range shape for mammals and birds found that the geometric constraints caused by the continental shape of South America and Africa indeed limit longitudinal range extents stronger than climate gradients (Castro‐Insua et al , ). To our knowledge, there are no similar studies of global gradients in plant range shapes.…”
Section: Equilibrial Limits: Variation In Ranges That Are Static Thromentioning
confidence: 99%
“…relative longitudinal and latitudinal extent) can help disentangle the importance of barriers compared to environmental gradients (Brown & Maurer, ). For instance, a study of gradients in range shape for mammals and birds found that the geometric constraints caused by the continental shape of South America and Africa indeed limit longitudinal range extents stronger than climate gradients (Castro‐Insua et al , ). To our knowledge, there are no similar studies of global gradients in plant range shapes.…”
Section: Equilibrial Limits: Variation In Ranges That Are Static Thromentioning
confidence: 99%
“…Range shape, the ratio between the latitudinal and longitudinal extent of a range, can be used to further detect dispersal limitations in underfilled ranges (Baselga et al., 2012). Under neutral ecological dynamics (Hubbell, 2001), a species should expand its range equally in all directions, resulting in circular ranges with shape ratios equal to 1 (Cain, 1944; Castro‐Insua et al., 2018). Such ranges are limited by a species' intrinsic dispersal ability, influenced by its functional traits (Cain, 1944; Castro‐Insua et al., 2018; Rapoport, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Under neutral ecological dynamics (Hubbell, 2001), a species should expand its range equally in all directions, resulting in circular ranges with shape ratios equal to 1 (Cain, 1944; Castro‐Insua et al., 2018). Such ranges are limited by a species' intrinsic dispersal ability, influenced by its functional traits (Cain, 1944; Castro‐Insua et al., 2018; Rapoport, 1982). Species with greater dispersal distances, more abundant propagules, shorter generations, or generalist ecological preferences should have advantages during establishment (Angert et al., 2011); this lack of intrinsic limitations allows such species to attain larger ranges (Baselga et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers investigating the effects of climate and its interaction with land‐use change on biodiversity often use the term “ climatic niche ” (e.g. Castro‐Insua, Gomez‐Rodriguez, Svenning, & Baselga, ; Dallas, Decker, & Hastings, ; Sapes, Serra‐Diaz, & Lloret, ; Sunday, Bates, & Dulvy, ), which aims to reflect the climatic elements of a species' multidimensional niche sensu Hutchinson (Hutchinson, ; Sapes et al, ). Within a species' fundamental niche (Hutchinson, ), the climatic elements encompass the species' climatic tolerances, which are often estimated through physiological tests (Frishkoff et al, ; Peterson et al, ).…”
Section: Introductionmentioning
confidence: 99%